A new ape from Türkiye and the radiation of late Miocene hominines - Ayla Sevim-Erol; David R. Begun; Alper Yavuz; Erhan Tarhan; Çilem Sönmez Sözer; Serdar Mayda; Lars W. van den Hoek Ostende; Robert M. G. Martin; M. Cihat Alçiçek (Communications Biology, 2023)
Abstract Fossil apes from the eastern Mediterranean are central to the debate on African ape and human (hominine) origins. Current research places them either as hominines, as hominins (humans and our fossil relatives) or as stem hominids, no more closely related to hominines than to pongines (orangutans and their fossil relatives). Here we show, based on our analysis of a newly identified genus, Anadoluvius, from the 8.7 Ma site of Çorakyerler in central Anatolia, that Mediterranean fossil apes are diverse, and are part of the first known radiation of early members of the hominines. The members of this radiation are currently only identified in Europe and Anatolia; generally accepted hominins are only found in Africa from the late Miocene until the Pleistocene. Hominines may have originated in Eurasia during the late Miocene, or they may have dispersed into Eurasia from an unknown African ancestor. The diversity of hominines in Eurasia suggests an in situ origin but does not exclude a dispersal hypothesis.